1998
DOI: 10.1038/sj.bmt.1701076
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram abnormality and high-dose busulfan in conditioning regimens for stem cell transplantation

Abstract: Summary: Patients and methodsBetween June 1989 and November 1996, a total of 22 High-dose busulfan (BU) is widely used in combined chemotherapy before allogeneic or autologous bone patients with various hematological malignancies or immunodeficiencies received allogeneic BMT (14 cases) or marrow transplantation. Convulsions are reported as a side-effect of high-dose BU. We recorded electroenceautologous peripheral blood stem cell transplants (eight cases) after preparation with high-dose BU (Table 1). Thirphal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…In adults, seizures typically occur in the 3 rd or 4 th day of Bu administration, probably as a result of drug accumulation [36,40-44] . Even without overt seizure activity EEG abnormalities can occur in up to 60% of patients [42] . Various anticonvulsant medications have been used for seizure prophylaxis including phenobarbital sodium, benzodiazepines (clonazepam, lorazepam) and phenytoin [41,42,45-47] .…”
Section: Clinical Experience Therapeutic Results and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, seizures typically occur in the 3 rd or 4 th day of Bu administration, probably as a result of drug accumulation [36,40-44] . Even without overt seizure activity EEG abnormalities can occur in up to 60% of patients [42] . Various anticonvulsant medications have been used for seizure prophylaxis including phenobarbital sodium, benzodiazepines (clonazepam, lorazepam) and phenytoin [41,42,45-47] .…”
Section: Clinical Experience Therapeutic Results and Toxicitymentioning
confidence: 99%
“…Even without overt seizure activity EEG abnormalities can occur in up to 60% of patients [42] . Various anticonvulsant medications have been used for seizure prophylaxis including phenobarbital sodium, benzodiazepines (clonazepam, lorazepam) and phenytoin [41,42,45-47] . Phenytoin has been widely used for seizure prophylaxis in patients receiving Bu as part of the conditioning regimen due to its non-sedating properties.…”
Section: Clinical Experience Therapeutic Results and Toxicitymentioning
confidence: 99%
“…However, two patients (cases 2 and 11) developed generalized seizure despite phenytoin prophylaxis. We have previously reported that patients receiving BU can show electroencephalogram (EEG) abnormalities without having clinical symptoms, 24 especially older children. Therefore, it may be necessary to monitor the serum concentration of BU and administer antiepileptics during the conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for transplantation were acute lymphoblastic leukemia in 31 patients (14 in first complete remission: 1CR), acute myelogenous leukemia in 14 (nine in 1CR), aplastic anemia in nine, non-Hodgkin's lymphoma in seven, myelodysplastic syndrome in four, rhabdomyosarcoma in three, Wiscott-Aldrich syndrome in three, chronic myelogenous leukemia in two, juvenile chronic myelogenous leukemia, neuroblastoma, fibrosarcoma, and yolk sac tumor in one each. Fifty-nine patients received intrathecal methotrexate (MTX) and cytarabine (AraC), and five received cranial irradiation (20)(21)(22)(23)(24) as central nervous system (CNS) prophylaxis before transplantation. We conducted careful neurological examinations according to the protocol of Hokkaido University School of Medicine Department of Pediatrics.…”
mentioning
confidence: 99%
“…Also, electroencephalogram abnormalities have been reported in patients receiving busulfan who did not experience seizures, confirming its neurotoxic effects. [11][12][13][14] Busulfan freely crosses the blood-brain barrier to achieve significant concentrations in the central nervous system. Busulfan concentrations in the central nervous system are similar to plasma concentrations, which most likely accounts for the neurotoxicity seen with high-dose busulfan.…”
mentioning
confidence: 99%